A method for minimizing the zone of low water flow velocity in a bottom center drain circular aquaculture tank. Issue 6 (13th May 2021) - Sin, Myong‐Guk; An, Chol‐Ho; Cha, Sang‐Jin; Kim, Myong‐Jin; Kim, Hyon‐Nam
Abstract: Bottom center drain circular tanks in which water is injected tangentially to the tank wall are widely used in aquaculture. However, a torus‐shaped region about the center drain can develop into an irrotational zone that generates low velocities and poor mixing. Many works have been devoted to improving tank hydraulics by making good use of the water flow pattern. However, mathematics‐friendly methods, such as the statistical optimization method, which is widely used in science and engineering, are rarely used in aquaculture tank designing. This work focuses on the minimization of the low velocity zone in a bottom center drain tank based on experimental planning and computational fluid dynamics. Model validation was carried out by comparison with measurements. The results show that the low velocity zone can be reduced measurebly by the proposed method.